Unusual polymethylene-interrupted, Δ5 monounsaturated and omega-3 fatty acids in sea urchin (Arbacia punctulata) from the Gulf of Mexico identified by solvent mediated covalent adduct chemical ionization mass spectrometry. (1st March 2022) - Wang, Dong Hao; Wang, Zhen; Li, Xu; Martinez, Secilia; James, Genevieve; Rahman, Md Saydur; Brenna, J. Thomas
Graphical abstract: Highlights: Sea urchin ( uni ) gonad fatty acids were comprehensively characterized. Unusual PMI-PUFA posing analytical challenges were identified by SM CACI-MS/MS. FA double bond isomers were completely distinguished/resolved by diagnostic ions. >100 sea urchin fatty acids were identified without standards and quantified. Sea urchin is a unique dietary source of PMI-PUFA. Abstract: Sea urchin (class Echinoidea) gonads are a prized delicacy in Japan and many other world cultures. The complexity of its fatty acid (FA) profile, particularly minor FA, presents a formidable analytical challenge. We applied solvent mediated (SM) covalent adduct chemical ionization (CACI) tandem mass spectrometry to comprehensive de novo structural and quantitative characterization of the FA profile of Gulf of Mexico Atlantic sea urchin (Arbacia punctulata). >100 FA were detected including many with unusual double bond structure. Gulf sea urchin gonad lipids are rich in Δ5 monounsaturated FA 20:1(5Z) at 2.7% and the polymethylene-interrupted (PMI) diene 20:2(5Z, 11Z) at 4.9%, as well as common omega-3 eicosapentaenoic acid (EPA; 5Z, 8Z, 11Z, 14Z, 17Z) at 9.8%±3.1% and arachidonic acid (AA; 5Z, 8Z, 11Z, 14Z) at 6.1%±2.1%. We propose plausible desaturation/elongation-based biochemical pathways for the endogenous production of unusual unsaturates. Unusual unsaturates may modify mammalian signaling and present novel bioactivities.